OCULAR HEALTH IN SCHOOLCHILDREN AND THE NURSES' PRACTICE IN PRIMARY HEALTHCARE - Raquel Malta Fontenele; Ana Inês Sousa; Alexandra Schmitt Rasche (Universidade Federal do Paraná, 2016)
The aim was to describe the profile and the practices of the nurses of the Family Health Team geared towards ocular health in schoolchildren. It is a descriptive study, in a Planning Area (PA) of the municipality of Rio de Janeiro, undertaken in May - June 2013. Among the actions, emphasis is placed on the number - 62 (66%) - of the nurses who identified impaired visual acuity during the nursing consultation, and those who asserted - 17 (18.08%) - that they had undertaken health actions in the schools. It is evidenced that all of those interviewed indicated the need to receive information on the visual acuity test. The actions directed towards schoolchildren's ocular health need to be improved, with emphasis placed on extending the nurse's work to include actions in the ambit of the school community. Periodical updating on the issue is recommended, along with encouragement to adopt routine practices in the health promotion and prevention actions undertaken in the schools, favoring improvements in the quality of the care offered.